Notes to Philosophy 167: Class 3 -- Kepler's Astronomia Nova: The Orbit of Mars -- Part 14. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Kepler's Original Justification for the Two "Laws": The Context of Discovery versus the Context of Justification -- The Evidential Argument for the Latitudes of Mars -- The Evidential Argument for the Ellipse -- The Evidential Argument for the Area Rule -- Some Standard Objections to the Arguments -- A Contrasting View of Scientific Evidence -- A Defense of the Evidential Arguments for Mars -- Select Sources.; Generally corresponds to the video segment: Class 3, Part 14.